Microscopic assessment of dentinal defects induced by ProTaper Universal, ProTaper Gold, and Hyflex electric discharge machining rotary file systems - An in vitro study - Takhellambam Premlata Devi; Amandeep Kaur; Shamurailatpam Priyadarshini; B S Deepak; Sumita Banerjee; Ng Sanjeeta (Wolters Kluwer Medknow Publications, 2021)
Background: Biomechanical preparation of root canal can damage root dentin leading to the formation of dentinal cracks which can eventually lead to fracture and failure of the treatment. Aim: The aim was to investigate the incidence of dentinal defects in root canals prepared with ProTaper Universal, ProTaper Gold, and Hyflex electric discharge machining (EDM) rotary file systems using handheld USB digital microscope. Materials and Methods: One hundred and fifty extracted mandibular premolar teeth with single canal were randomly divided into five groups (n = 30). Group 1: unprepared (negative control). Group 2: canal preparation done with nickel-titanium hand files (positive control), Group 3: canals prepared with ProTaper Universal rotary system, Group 4: canal preparation done with ProTaper Gold rotary system, and Group 5: canals prepared with Hyflex EDM rotary system. The specimens were sliced at 3 mm, 6 mm, and 9 mm from the apex with a slow-speed saw under water cooling. Digital images of each section were captured at ×40 magnification with the aid of a microscope. Two independent evaluators assessed the images for the presence of dentinal defects. The number of dentinal defects was recorded and Chi-square test was used for statistical analysis (P < 0.05). Results: The number of specimens presenting dentinal defects was as follows: Group 3; ProTaper Universal - 9/30 (30.0%), Group 4; ProTaper Gold - 2/30 (6.7%), and Group 5; Hyflex EDM - 1/30 (3.3%). No defects were detected in the negative and positive control groups (Group 1 and Group 2). Conclusion: ProTaper Universal showed the highest percentage of defects in comparison to ProTaper Gold and Hyflex EDM.